INFLUENCE OF ROCK PROPERTIES ON TBM RATE OF PENETRATION - Maximkyzy, Alfiya (School of Mining and Geosciences, 2023)
For the purpose of selecting the best tunnel boring machine (TBM) in varied ground conditions, the properties of intact rock and rock mass should be thoroughly examined. This is because machine performance is significantly impacted by the properties of rock mass. The aim of this thesis is to evaluate how rock mass characteristics affect the performance of TBM by developing a new formula based on empirical data to estimate TBM performance. To this end, a database containing two tunnel constructions, the Queens Water Tunnel which is in New York, USA, and Karaj-Tehran water conveyance tunnel project from Iran, has been compiled. The parameters considered as inputs for the model were the uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), quartz content, spacing, Q-system, density, and Cerchar abrasion index (CAI). The model output was the rate of penetration (ROP). In order to develop an empirical equation that can estimate the TBM ROP, both linear and non-linear regressions have been carried out. The results indicated that multiple non-linear regression analysis should be utilized in the context of both tunnel projects for calculating the rate of penetration of TBM. Moreover, the correlation between the penetration rate, rock mass characteristics, and intact rock properties was investigated, and the resulting relationships are presented and analyzed here.
Keywords: Type of access: Restricted; tunnel boring machine; rock properties